2013
DOI: 10.1590/s1415-47572013000400020
|View full text |Cite
|
Sign up to set email alerts
|

Dmp53, basket and drICE gene knockdown and polyphenol gallic acid increase life span and locomotor activity in a Drosophila Parkinson's disease model

Abstract: Understanding the mechanism(s) by which dopaminergic (DAergic) neurons are eroded in Parkinson’s disease (PD) is critical for effective therapeutic strategies. By using the binary tyrosine hydroxylase (TH)-Gal4/UAS-X RNAi Drosophila melanogaster system, we report that Dmp53, basket and drICE gene knockdown in dopaminergic neurons prolong life span (p < 0.05; log-rank test) and locomotor activity (p < 0.05; χ2 test) in D. melanogaster lines chronically exposed to (1 mM) paraquat (PQ, oxidative stress (OS) gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 55 publications
3
8
0
Order By: Relevance
“…Our data show that JNK is activated by phosphorylation following PQ treatment, while pharmacological inhibition of JNK increases survival in WT flies. In accordance with our data, knockdown of the basket gene in the dopaminergic neurons has been shown to improve survival and climbing ability in Drosophila 68 . Prolonged JNK activation has been implicated in exacerbating disease phenotypes in both AD and PD models 69,70 .…”
Section: Discussionsupporting
confidence: 91%
“…Our data show that JNK is activated by phosphorylation following PQ treatment, while pharmacological inhibition of JNK increases survival in WT flies. In accordance with our data, knockdown of the basket gene in the dopaminergic neurons has been shown to improve survival and climbing ability in Drosophila 68 . Prolonged JNK activation has been implicated in exacerbating disease phenotypes in both AD and PD models 69,70 .…”
Section: Discussionsupporting
confidence: 91%
“…The previous outcome may be attributed to the polyphenolic and other phytochemical constituents that were recorded in the GC-MS analysis of PSE and PJ. Our results were in agreement with Ortega-Arellano et al [ 46 ] who recorded a protective effect of polyphenols against PQ in Drosophila.…”
Section: Discussionsupporting
confidence: 94%
“…Apoptosis or programmed cell death was potentiated following PQ administration into Drosophila melanogaster via the oxidative stress-induced pathway [ 46 ]. The molecular cascades for apoptosis were inferred to ROS production and chromatin condensation/DNA fragmentation [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, polyphenols are identified to be neuroprotective for multiple human neurodegenerative diseases including PD, Huntington’s disease (HD) and amyotrophic lateral sclerosis (ALS) [50]. It was reported that polyphenols, including GA, propyl gallate (PG), epicatechin (EC), EGC, and EGCG, can protect DA neurons and restore the impaired movement activity induced by iron and/or paraquat (PQ) challenges in Drosophila PD model [51,52]. Furthermore, green and black tea polyphenol extracts, as well as EGCG, were identified to be able to protect against MPTP or 6-OHDA challenges induced DA neurons degeneration in mice, rats and monkey PD models [53,54].…”
Section: Discussionmentioning
confidence: 99%